ADDITIVE EFFECT OF GENES POLYMORPHISM OF FOLATE CYCLE PROTEINS AND HOMOCYSTEIN LEVEL IN PATIENTS WITH PROLIFERATIVE DISEASES OF THE BREAST AS A POTENTIAL FACTOR OF THE RISK OF THROMBOSSES - Aleksandr V. Markovsky («REMEDIUM GROUP» Ltd., 2018)
Aim. The aim of study was to examine the relationship between serum and mammary gland homocysteine levels with the carrier of separate SNP (single nucleotide polymorphism) genes of the folate metabolism system in patients with proliferative diseases and breast cancer. Methods and results. The study included 182 patients with proliferative diseases of the mammary gland in transbaikalia. The control group included 144 women who did not have oncological diseases. The serum homocysteine level and the supernatant of the mammary tissue homogenate were evaluated by high performance liquid chromatography. Genotyping for the detection of polymorphism MTHFRС677T, MTHFRА1298C, MTRA2756G, MTRRA66G was carried out by polymerase chain reaction with the detection of the amplification product in real time. In the course of molecular genetic testing in patients with proliferative diseases of the mammary gland, there was found: 1) the absence of an explicit association of the carriage of genetic polymorphism MTHFRС677T, MTHFRА1298C, MTRA2756G and MTRRA66G with serum homocysteine concentration, however, comparative hyperhomocysteinemia and, to a lesser extent, in women with the benign breast diseases; 2) the highest homocysteine content in the blood in patients with breast cancer whose genotype was characterized by combinations of polymorphic alleles MTR2756G x MTRR66G; 3) that the MTR2756A allele and genotype MTHFR1298AC, especially their combination of MTHFR1298AC x MTR2756A, increase the risk of developing benign breast formations; 4) the effect of the risk alleles MTR2756G and MTRR66GON the concentration of homocystein in the tumor tissue of the mammary gland. Conclusion. These patterns indicate a certain contribution of the polymorphisms studied, especially their additive effect, both in the development of proliferative diseases of the mammary gland and in the possible potentiation of prothrombotic effects in these patients against the background of tumor progression and homocysteine metabolism disorders.